(untitled) (Docentes 2.0 Journal, 2026)
The integration of artificial intelligence (AI) into higher education has driven a significant transformation in educational processes. This study aimed to explore undergraduate students’ perceptions of their academic experience with ChatGPT 3.5 as an academic support tool in a business school at a Peruvian university during 2023. The research followed the pragmatic paradigm, the analytical-synthetic method, and a mixed approach, with a convergent case study design, triangulation, and a cross-sectional scope. The sample included 178 Business Administration students, who answered a questionnaire with eight closed-ended questions and four open-ended questions, which sought to identify their knowledge, experiences, and attitudes toward AI. The results showed a predominantly positive perception of ChatGPT and highlighted its contribution to autonomous study, content comprehension, and the development of analytical and creative skills. Participants valued its usefulness for access to reliable information, rapid resolution of doubts, and reinforcement of their capacity for academic innovation. The analysis also showed that confidence in the tool and familiarity with its use increased their willingness to integrate it into future academic experiences. Overall, the results provide relevant empirical evidence on ChatGPT’s potential as a pedagogical resource and underscore the need to promote institutional policies directed toward digital literacy and AI ethics.